(untitled) (Global Journal of Science Frontier Research, 2014)
Laser induced breakdown spectroscopy (LIBS) was used to determine the elemental content of Rice and Husk which were collected from Bangladesh Rice Research Institute (BRRI) in Gazipur, Bangladesh (latitude: 24.0958 0 N, longitude: 90.4125 0 E). Samples were collected from one experimental plot. Several elements such as Ni, Cu, Zn, Fe, Ca, Al, Si, Na, K, Ti, Mn, Li, Mo, Co, Mg, C were identified in Rice and husk samples by Laser Induced Breakdown Spectroscopy.